Record Linkage Strategies: Part II. Portable Software and Deterministic Matching - Wajda, A.; Roos, L. L.; Layefsky, M.; Singleton, J. A. (Methods of Information in Medicine, 1991)
Software to perform record linkage should have several characteristics: (1) portability in being able to function with researchers’ current arrangement of computer systems and languages, (2) flexibility in handling different linkage strategies, and (3) low cost in both computer time and researchers’ efforts. A linkage package (LINKS) is described which satisfies these criteria; LINKS provides tools for both deterministic and probabilistic linkage as well as test modules for assessing data quality and structure. Because each linkage project is different, the modular nature of the software allows for better control of the programming process and development of unique strategies. Since the user provides the weights and decision rules, he may modify data between steps and/or develop extra steps to supplement the basic modules. In two information-rich linkage projects involving California AIDS data, LINKS identified mortality using deterministic approaches and permitted comparisons with other software and strategies. Flexible software and a deterministic approach would have eliminated the expensive key entry used to add full names and social security numbers as additional identifiers to one of the California data files.
Keywords: Record Linkage; Software; Data Banks; AIDS